Property insurance, portfolio selection and their interdependence - Fwu-Ranq Chang (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper studies the interdependence between property insurance and portfolio selection. The insurance premium of property loss is shown to play the role of subsistence consumption in the analysis. Then, security becomes a necessity good and an increase in any insurance parameter would make the investor more conservative. The effect of a stock market parameter on the marginal propensity to insure is shown to be opposite that on the marginal propensity to consume. Consequently, an increase in volatility would encourage those with a greater-than-unity relative risk aversion to purchase more insurance at the expense of current consumption.
Keywords: G11; G22; E21; 330; insurance premium; subsistence consumption; portfolio substitution; optimal saving under uncertainty; Sachversicherung; Versicherungsprämie; Sparen; Konsumtheorie; Zeitpräferenz; Portfolio-Management; Theorie